Community-Based Training and Mentoring on Interactive E-LKPD Development for Mathematics Teachers in MTs Sleman Regency - Iqbal Ramadani; Nidya Ferry Wulandari; Dian Permatasari (Indonesian Scientific Journal, 2026)
The development of interactive Electronic Student Worksheets (E-LKPD) plays an important role in supporting technology-integrated mathematics learning. However, many teachers still face challenges in developing interactive E-LKPD, particularly related to technical and pedagogical skills. This article aims to describe the implementation and outcomes of a community service program in the form of community-based training and mentoring on interactive E-LKPD development for mathematics teachers at Madrasah Tsanawiyah (MTs) in Sleman Regency. The program was conducted fully online in 2025 and involved 30 mathematics teachers who are members of the MTs Mathematics Teacher Working Group (MGMP). A Community-Based Research (CBR) approach was employed, consisting of preparation, training implementation, and mentoring stages. Program evaluation was carried out qualitatively by collecting participants’ feedback, comments, and suggestions. The results indicate an improvement in teachers’ ability to develop interactive E-LKPD, positive perceptions of the training and mentoring activities, and teachers’ intentions to implement interactive E-LKPD in mathematics instruction. Nevertheless, several challenges were identified, including limited digital experience and technical constraints. Overall, the findings suggest that community-based training and mentoring have the potential to provide sustainable impact in enhancing mathematics teachers’ digital pedagogical competence.